2018
DOI: 10.1101/336016
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The cargo receptor SURF4 promotes the efficient cellular secretion of PCSK9

Abstract: Proprotein convertase subtilisin/kexin type 9 (PCSK9) is a secreted protein that plays an important role in regulating plasma cholesterol and cardiovascular disease risk. PCSK9 secretion uniquely depends on the cytoplasmic COPII protein SEC24A, suggesting the presence of a transmembrane ER cargo receptor mediating this interaction. Here, we report a novel approach that combines proximity-dependent biotinylation and proteomics together with genome-scale CRISPR screening to identify proteins that facilitate the … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
3

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(23 citation statements)
references
References 56 publications
1
19
3
Order By: Relevance
“…Additional examples from recent studies include a variety of receptor systems and cargo proteins-Vti1a/b for Golgi export of Neuropeptide-Y (44), SURF4 for the secretion of PCSK9 (45), and p24 for ER export of GPI-anchored proteins (46). Bulk flow or lower-affinity binding to other cargo receptors can explain slower cargo transport (47).…”
Section: Discussionmentioning
confidence: 99%
“…Additional examples from recent studies include a variety of receptor systems and cargo proteins-Vti1a/b for Golgi export of Neuropeptide-Y (44), SURF4 for the secretion of PCSK9 (45), and p24 for ER export of GPI-anchored proteins (46). Bulk flow or lower-affinity binding to other cargo receptors can explain slower cargo transport (47).…”
Section: Discussionmentioning
confidence: 99%
“…Our screen was designed to focus on post-transcriptional regulators of EPO by placing its expression under the control of a CMV promoter. Screening strategies similar to the one employed in this manuscript and in a recently published report (32) might help identify additional ER cargo receptors for other soluble secreted proteins, and shed more light into the extent of the contribution of “cargo capture” to recruitment of cargos into COPII vesicles.…”
Section: Discussionmentioning
confidence: 90%
“…Erv29p recycles back from Golgi-to-ER via recognition of its well-conserved di-lysine sorting signal by the COPI coat (38). In mammalian cells, only a handful of cargos (APOB, PCSK9, DSSP, AMLEX, and GH) have been shown to depend on SURF4 for efficient secretion (32, 33, 39). However, a recent report demonstrated that mice with germline deletion of Surf4 exhibit early embryonic lethality (40) similar to C. elegans (33), suggesting the presence of one or more SURF4-dependent cargos with a critical function during embryogenesis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The mammalian homologs of yeast ER vesicle (Erv) proteins have also been thought to function as cargo receptors (Dancourt and Barlowe, 2010). One of these proteins, SURF4, binds amino-terminal tripeptide motifs of soluble cargo proteins and regulates ER export of soluble cargo proteins including the yolk protein VIT-2 in Caenorhabditis elegans (Saegusa et al, 2018), and PCSK9 and apolipoprotein B in mammalian cells (Emmer et al, 2018;Yin et al, 2018).…”
Section: Introductionmentioning
confidence: 99%